Nanotechnology: An Emerging Area of Scientific Issues and Legal Challenges - Mathew, Thomas (Kathmandu School of Law Review, 2013)
Nanotechnology is based on the convergence of several disciplines of science and technology. India though entering late in this field has been able to make a mark, however, there is a long way to go both in the scientific and legal arena. This paper initially focuses on the scientific development of nanotechnology in India and thereafter on various acts and regulations that deal with nanotechnology in India.